2009
DOI: 10.4269/ajtmh.2009.80.914
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artemisinin-Based Combination Therapy for Treatment of Persons with Uncomplicated Plasmodium falciparum Malaria in West Sumba District, East Nusa Tenggara Province, Indonesia, and Genotypic Profiles of the Parasite

Abstract: Reports on treatment failures associated with the use of first-and second-line antimalarial drugs chloroquine and sulfadoxine-pyrimethamine have recently increased in many parts of Indonesia. The present study evaluated artemisinin-based combination therapy for treatment of persons with uncomplicated Plasmodium falciparum malaria in West Sumba District, East Nusa Tenggara Province. A total of 103 persons 1-57 years of age were enrolled, given standard artesunate-amodiaquine therapy, and followed-up for 28 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…In this study P. falciparum isolates frequently carried the allelic combination of pfcrt 76T and pfmdr1 86Y, but previous study showed artesunate (AS) and AQ combination therapy to be highly effective [10]. This finding suggests that the parasite haplotype 76T and pfmdr 1 86N is still sensitive to AQ treatment, particularly in combination with AS.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this study P. falciparum isolates frequently carried the allelic combination of pfcrt 76T and pfmdr1 86Y, but previous study showed artesunate (AS) and AQ combination therapy to be highly effective [10]. This finding suggests that the parasite haplotype 76T and pfmdr 1 86N is still sensitive to AQ treatment, particularly in combination with AS.…”
Section: Discussionmentioning
confidence: 82%
“…Resistance to CQ was first reported in 1975, resistance to SP appeared in 1978, and by 1997 treatment failures associated with both drugs had been documented in most provinces [5,6]. Molecular epidemiology studies conducted from 2003 to 2005 in several sentinel sites throughout the Indonesia archipelago indicated widespread distribution of mutant alleles associated with resistance to CQ resistance ( pfmdr1 86Y, Plasmodium falciparum chloroquine resistance (pfcrt) 76T) and SP ( dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps)) [7-10]. The mutant allele associated with chloroquine resistance, pfcrt 76T, seems to be nearly fixed among the P. falciparum isolates collected, and pfmdr1 1042D alleles were mainly found in the island of Flores [9].…”
Section: Introductionmentioning
confidence: 99%
“…Of them, six treatment regimens were evaluated in Western Cambodia and one study was of a single dose of artesunate (see Additional file 8). In the remaining two studies [18,19] patients were treated with a three-day AS+AQ in Senegal and Indonesia and with PPRday3 documented as 10% (95%CI =6.3-15.6%) and 12.6% (95% CI=7.5-20.4%) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Using this definition, nine outliers were identified, six of which were from the Pailin region, the epicentre for emerging artemisinin resistance in Cambodia and one of which was a short-course regimen. Of the remaining two studies, one by Asih et al from Indonesia conducted in 2005 to 2006, combined PCR positivity with microscopy, which may have accounted for higher than expected proportion of patients parasitaemic on Day 3 [19]. The remaining trial arm in a study by Adjuik et al was conducted in Senegal, although the Day 3 value was derived from a figure rather than actual data [18], (see Additional file 8).…”
Section: Discussionmentioning
confidence: 99%
“…Although very little is known of the malaria vector bionomics in this area, one entomologic survey documented 11 species of anophelines occurring in this district: Anopheles sundaicus, Anopheles subpictus, Anopheles barbirostris, Anopheles hyrcanus, Anopheles aconitus, Anopheles flavirostris, Anopheles annularis, Anopheles maculatus, Anopheles tessellatus, Anopheles vagus, and Anopheles kochi. 18 These species occurred in relative abundance in accordance with their respective preferred habitats including coastal marshes and ponds, seasonal rice paddies, and forested hillsides. This setting is typical for many rural malaria-endemic areas in Indonesia, particularly high risk coastal zones.…”
Section: Methodsmentioning
confidence: 99%